Impact of Covid-19 on the Portuguese banking sector - Yetao, Xu (2022)
The entire impact of COVID-19 has yet to be determined. However, it has become evident that the virus has infected banks and financial markets, resulting in severe reductions in global capital flows. The purpose of this study is to find the elements that influence the profitability of banks in Portugal and the impact of the pandemic on the Portuguese banking industry. To achieve the goals of this study, the performance of 26banksin Portugal is assessed in terms of return on assets from 2016 to 2021. The dependent variable(ROA) is regressed on independent variables including asset utilization, bank size, equity multiplier and operating costs. According to the findings, the profitability of the Portuguese banking sector fell from 0.42 percent in 2019 to 0.06 percent in 2020. In terms of the econometric findings, it's worth noting that while asset utilization ratio has a positive and significant impact on bank profitability, increased operating costs will greatly reduce ROA.